Glycemic Improvement with a Fixed‐dose combination of DPP‐4 inhibitor + metformin in patients with Type 2 diabetes (GIFT study) - Bajaj, Harpreet S.; Ye, Chenglin; Jain, Esha; Venn, Karri; Stein, Eden; Aronson, Ronnie (Diabetes, obesity & metabolism, 2018)
This study investigates changes in A1C following a switch from dual therapy of metformin and DPP‐4 inhibitor to a fixed‐dose combination (FDC) of metformin + DPP‐4 inhibitor following the introduction of the FDC in the provincial formulary. The LMC Diabetes Registry was queried retrospectively for patients with type 2 diabetes, aged between 18 and 80 years with at least one A1C recorded prior and ≥3 months post‐switch. Five hundred and sixty‐eight subjects with mean age 64 ± 12 years and mean A1C 7.7% ± 1.2% met study criteria. Overall, A1C was 0.3% lower post‐switch to FDC (P < .01). In stratified analysis, subjects with baseline A1C between 7% and 10% had 0.4% lower A1C (P < .01), with 31% of these subjects reaching target A1C ≤7%, post‐switch. A1C reduction was greater among patients with a higher baseline pill burden: 0.4% among those using ≥10 pills/day vs. 0.1% for those with <10 pills/day (P = .02). In this real‐world study, switching to FDC of metformin + DPP‐4 inhibitor was associated with a significant improvement in A1C. Switching to FDC, especially in patients with high pill burden, can improve A1C goal achievement in clinical practice.